2018
DOI: 10.1177/0743915618811850
|View full text |Cite
|
Sign up to set email alerts
|

Anticonsumption as Tactical Response to Institutionalized Subordination: The Case of Materially Deprived Anticonsumers

Abstract: Whereas most anticonsumption research focuses on middle-to upper-class consumers who reduce, avoid, or control consumption, this study analyzes anticonsumption among materially deprived consumers. Such an anticonsumption focus runs contrary to the conventional subordination of homeless people to the status of inferior and deficient, whose survival is dependent on social housing support and food charities. Findings from an ethnographic study in Australia show that materially deprived consumers avoid social hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
(115 reference statements)
0
13
0
2
Order By: Relevance
“…Figure shows the largest clusters of theoretical and empirical interest that scholars subsume under the umbrella of anticonsumption. The most prominent cluster focuses on consumer resistance (i.e., Amine & Gicquel, ; Chalamon, ; Izberk‐Bilgin, ; Nepomuceno & Laroche, ), followed by green/sustainable consumption (e.g., Black, ; Black & Cherrier, ; Garcia‐de‐Frutos & Ortega‐Egea, ), boycotts/consumer activism (e.g., Makarem & Jae, ), voluntary simplicity (i.e., Craig‐Lees & Hill, ; Shaw & Newholm, ), brand/product/product category avoidance (e.g., Cherrier & Hill, ; Lee et al, 2009), ethical/moral consumption (e.g., Eckhardt et al, ; Sudbury‐Riley & Kohlbacher, ; Thompson, ), alternative consumption (e.g., Anderson, Hamilton, & Tonner, ; Ozanne & Ballantine, ), and symbolic consumption (e.g., Hogg, Banister, & Stephenson, ).…”
Section: State‐of‐the‐art In Anticonsumption Researchmentioning
confidence: 99%
“…Figure shows the largest clusters of theoretical and empirical interest that scholars subsume under the umbrella of anticonsumption. The most prominent cluster focuses on consumer resistance (i.e., Amine & Gicquel, ; Chalamon, ; Izberk‐Bilgin, ; Nepomuceno & Laroche, ), followed by green/sustainable consumption (e.g., Black, ; Black & Cherrier, ; Garcia‐de‐Frutos & Ortega‐Egea, ), boycotts/consumer activism (e.g., Makarem & Jae, ), voluntary simplicity (i.e., Craig‐Lees & Hill, ; Shaw & Newholm, ), brand/product/product category avoidance (e.g., Cherrier & Hill, ; Lee et al, 2009), ethical/moral consumption (e.g., Eckhardt et al, ; Sudbury‐Riley & Kohlbacher, ; Thompson, ), alternative consumption (e.g., Anderson, Hamilton, & Tonner, ; Ozanne & Ballantine, ), and symbolic consumption (e.g., Hogg, Banister, & Stephenson, ).…”
Section: State‐of‐the‐art In Anticonsumption Researchmentioning
confidence: 99%
“…Ample research has shown that having or lacking power influences a wide range of measures of consumer well-being, including perceptions of price unfairness (Jin, He, and Zhang 2014), choice of health care treatments and providers (Anderson et al 2016), anticonsumption activities (Cherrier and Hill 2018), and saving behaviors (Garbinsky, Klesse, and Aaker 2014) (for a review, see Rucker, Galinsky, and Dubois [2012]). However, limited research has examined whether and how consumers’ sense of power influences their food purchase decisions and food choices.…”
mentioning
confidence: 99%
“…In many of the discussions with researchers, and in their actions, these homeless men tried to differentiate themselves from other poor people who relied on public or private welfare systems. This work was followed by research into homeless living such as Cherrier and Hill (2018), who took a distinct path recognizing how women and men suffering from this condition used an anticonsumption response to institutions that provided support while simultaneously subordinating them. In both scenarios, it was clear that homelessness carried a stigma that resulted in self-talk and behaviors that eschewed this label.…”
Section: Framing Poverty and Stigma Researchmentioning
confidence: 99%